Pembacaan Dzikir Ratib Al-Attas dan Al-Haddad di Pesantren Modern Al-Qur’an Pekalongan: Studi Living Qur’an - Muhammad Afif Assegaf (Kuras Institute, 2024)
Living Qur'an research on the practice of dhikr ratib Al-Attas and Al-Haddad in Pondok Pesantren Modern Al-Qur'an Buaran Pekalongan shows the integration of the Qur'an in the daily routine of Muslims. Anthropological qualitative research explores the meaning of dhikr in this tradition. Primary data were obtained through online interviews and observations with Santri and administrators. The results show that the dhikr routine is directed by K.H. Abdul Aziz al-Hafidz and is considered an act of worship, a companion to religious learning, and a means of tranquility. In Talal Asad's theoretical framework, the dhikr tradition is the result of the interaction of religion and culture, becoming the identity of the pesantren. The conclusion shows that dhikr in this pesantren is not only an act of worship but also part of the educational objectives, especially the memorization of the Qur'an. This study provides an in-depth insight into the livelihood of the Qur'an in pesantren communities.